أثر التطفير باستخدام أشعة غاما في بعض الصفات الكمية في فول الصويا (Latakia University Journal -Biological Sciences Series, 2019)
عرضت بذور صنفين من فول الصويا هما (Sb149,Sb55) إلى ثلاث جرعات من أشعة غاما : Gy(200,150,100), بهدف معرفة تأثير أشعة غاما في بعض الصفات الاقتصادية في فول الصويا, و نفّذ هذا البحث في جامعة تشرين  في اللاذقية خلال موسمين زراعيين متتالين هما 2009 و2010, أحدثت الجرعات الثلاث تغيرات مورفولوجية، وتشوهات مختلفة، تناسبت طرداً مع زيادة الجرعة في كلا الصنفين, كما انخفضت نسبة النباتات الحية بعد شهر من الزراعة بزيادة الجرعة الإشعاعية أيضاّ. وكانت قيم معامل الاختلاف في جميع الجرعات وفي كلا الصنفين أعلى من الشاهد, وأظهرت النتائج أن الصنف Sb55 كان أقل حساسية لجرعات الأشعة الثلاثة من الصنف Sb149 , كما أظهر كل من الصنفين استجابة للأشعة في M1 وM2 أنعكس بعضها إيجابيا على شكل زيادة في عناصر الغلة في بعض النباتات المنتخبة, أو الباكورية في بعضها الآخر, حيث انتخبت العديد من النباتات الطافرة التي تفوقت على الشاهد في صفة عدد البذور في النبات , و وزن الــ100 بذرة خاصة في الجرعتين Gy(200,100) في كلا الصنفين , وبعضها الآخر وصل إلى مرحلة النضج الكامل أبكر من الشاهد بـــ(24) يوماً؛ كما هو الحال عند نباتات M2 الناتجة من تطفير الصنف (Sb149) بالجرعة (150Gy). Seeds from two soybeans Glycine max (L.) Merr varieties.(Sb149 , Sb55) were irradiated with three doses of gamma rays: 100, 150 and 200 Gy to examine the effect of Gamma Rays on some economic traits in soybeans. This research was conducted at Tishreen University, Lattakia for two successive seasons (2009,2010) .All three doses caused morphological variations and malformation which increased by increasing the dose in both varieties . Also the percentage of living plants after month of planting decreased by increasing the radiation dose . Variation coefficient for the two varieties in all doses was more than the control. The results revealed that the variety Sb55 was less sensitive to the three doses of radiation than the variety sb149 . The two varieties had responded to the radiation in both of the two generations (M1,M2) that some of them  reversed positively as an increase in yield for some of selected plants or early maturing in others . Many of mutative plants which were selected had more enhanced traits than the control, this was in number of seeds per plant and the weight of 100 seeds ,especially in the two doses (100,200) Gy in both of two varieties . Some of them were fully matured 24 days before control such as in the dose 150 Gy, Sb149 in the second generation M2.